Violation of Environmental Law as the Ground for Exclusion of Economic Operators from Public Procurement in Lithuania - Rudauskienė, Rimantė (Teisė, 2018)
The article focuses on the regulatory and implementation problems of exclusion of economic operators from public procurement procedures for violation of environmental law in Lithuania. It seeks to reveal the purpose, concept and content of this ground for exclusion, considers legal conditions, circumstances and possibilities for its application, elaborates on the legal scope and limits for implementation.